(untitled) (Dhaka University Journal of Biological Sciences, 2013)
Pseudomonas perfectomarina was isolated from a eutrophic bottom environment and introduced to stimulate heterotrophic and decomposing activities. The bacterial cells re-suspension was added to the experimental system after absorbing with porous substrates. The strain enhanced net regeneration of dissolved inorganic nitrogen and inorganic phosphorus from the sediment by two to fivefolds at different temperatures. The bacteria P. perfectomarina enhance net regeneration of 83.20, 148.08, 127.58 and 193.31 μM dissolved inorganic nitrogen and 14.12, 13.24, 14.43 and 23.21 μM dissolved inorganic phosphorous from the sediment at 20, 23, 24 and 26ºC, respectively. Results suggested that the application of P. perfectomarina with substrates would be promising for improvement of eutrophic sediment water interface during summer. Dhaka Univ. J. Biol. Sci. 22(1): 21-28, 2013 (January)